Low Serum Folate Level and Increased Risk of Invasive Cervical Cancer in Bangladeshi Women - Ferdous, Jannatul; Khatun, Sabera; Biswas, Subrata Kumar; Pervin, Shahana; Akter, Latifa; Keya, Kashfia Ahmed; Joarder, Mita; Khan, Jawad Mahruj (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): The aim of this study was to evaluate the risk of cervical cancer in relation to serum concentrations of folate. Materials and methods: This case-control study was conducted in the Gynaecologic Oncology Division of Bangabandhu Sheikh Mujib Medical University from November 2015-October 2016. For this study 50 patients with invasive cervical cancer were taken as study population and 50 healthy women of VIA or paps negative were taken as control to observe and compare serum folate level. Exclusion criteria were women with conditions associated with low folate level. Outcome variable was serum folate level and a p value of < 0.05 was considered as significant. Results: Most of the participants belonged to age group 35 to 55 years in both the groups. Most of the study cases had low income status than the control group. Maximum patients with cervical cancer took OCP in comparison to control. Majority of the patients with cervical cancer had significantly low level of serum folate (<2.7ng/ml) than those in the control group (2.7-16.1ng/ml), p=000. Conclusion: A significantly low level of serum folate, was observed in patients with invasive cervical cancer. So dietary interventions with folate supplementation might have some role in prevention of cervical carcinoma. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 23-27